Training volume and high-speed loads vary within microcycle in elite North American soccer players - Ishida, A.; Draper, G.; Wright, M.; Emerson, J.; Stone, M. H. (The Journal of Strength and Conditioning Research, 2023)
The purposes of this study were to reduce dimensionality of external training load variables and examine how the selected variables varied within microcycle in elite North American soccer players. Data were collected from 18 players during 2018-2020 in-seasons. Microcycle was categorized as 1, 2, 3, 4, 5 days before match day (MD-1, MD-2, MD-3, MD-4, and MD-5, respectively). Training load variables included total distance, average speed, maximum velocity, high-speed running distance (HSR), average HSR, HSR efforts, average HSR efforts, sprint distance, average sprint distance, sprint efforts, average sprint efforts, total PlayerLoad, and average PlayerLoad. The first principal component (PC) can explain 66.0% of the variances and be represented by "high-speed load" (e.g., HSR and sprint-related variables) with the second PC relating to "volume" (e.g., total distance and PlayerLoad) accounting for 17.9% of the variance. Average sprint distance and total distance were selected for further analysis. Average sprint distance was significantly higher at MD-3 than at MD-2 (p = 0.01, mean difference = 0.36 m•minute-1, 95% confidence intervals [CIs] = 0.07-0.65 m•minute-1) and MD-4 (p = 0.012, mean difference = 0.26 m•minute-1, 95% CIs = 0.10-0.41 m•minute-1). Total distance was significantly higher at MD-3 than at MD-1 (p < 0.001, mean difference = 1,465 m, 95% CIs = 1,003-1926 m), and MD-2 (p < 0.001, mean difference = 941 m, 95% CIs = 523-1,360 m). Principal component analysis may simplify reporting process of external training loads. Practitioners may need to choose "volume" and "high-speed load" variables. Elite North American Soccer players may accumulate higher average sprint distance at MD-3 than at other training days.